Inequalities in Action: Examining the Interplay of Social Origins and Right-to-Study in Shaping Student Employment Patterns - Bozzetti, Alessandro; De Luigi, Nicola; Vergolini, Loris (Italian Sociological Review, 2026)
The paper explores the intersection of social origins, Right-to-Study measures, and student employment among university students in Italy, with a focus on the University of Bologna. In particular, it investigates how parental education (as a proxy for cultural capital) influences the likelihood of working while studying and evaluates the efficacy of Right-to-Study benefits – namely, scholarships and tuition waivers - in mitigating the need for student employment. Findings indicate that students with lower parental education are significantly more likely to work extensively, even when controlling for economic resources; this suggests that cultural resources exert an independent effect on student behavior. Furthermore, results show that comprehensive financial support (i.e., the combination of both scholarships and waivers) effectively reduces the probability of working extensively, especially for students from disadvantaged educational backgrounds; in contrast, tuition waivers alone appear insufficient to alleviate financial pressures. Residential status further differentiates student experiences: off-site students are less likely to work extensively than residents or commuters, possibly reflecting higher motivation or selection effects, and Right-to-Study benefits seem particularly effective in supporting off-site students in reducing work hours. Drawing on survey data from the HousINgBO project (N = 9,337), these findings highlight the multifaceted nature of inequality in higher education and suggest that robust financial aid can partially offset inherited cultural disadvantages, with important implications for the design of Right-to-Study policies: effective support strategies should also consider cultural and symbolic barriers, particularly for first-generation and disadvantaged students.